2005
DOI: 10.1213/01.ane.0000141527.60441.b7
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Enhances Platelet-Neutrophil Adhesion in Whole Blood In Vitro

Abstract: Previous studies showed that alpha- or beta-adrenoceptor stimulation by catecholamines influenced neutrophil function, cytokine liberation, and platelet aggregability. We investigated whether adrenergic stimulation with epinephrine also alters platelet-neutrophil adhesion. This might be of specific interest in the critically ill, because the increased association of platelets and neutrophils has been shown to be of key importance in inflammation and thrombosis. For this purpose, whole blood was incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Nonetheless, when UK14304-pretreated human neutrophils were activated with IL-8, a chemokine widely implicated in neutrophil activation during the adhesion cascade (46), these cells reduced sensitivity to this chemokine in terms of L-selectin shedding and increased CD11b expression. This finding is consistent with the response of L-selectin and CD11b, which has been observed when neutrophils are activated with fMLP in the presence of epinephrine (62). Thus, our data suggest that signaling via the a2-adrenoceptor renders neutrophils less sensitive to proinflammatory mediators.…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, when UK14304-pretreated human neutrophils were activated with IL-8, a chemokine widely implicated in neutrophil activation during the adhesion cascade (46), these cells reduced sensitivity to this chemokine in terms of L-selectin shedding and increased CD11b expression. This finding is consistent with the response of L-selectin and CD11b, which has been observed when neutrophils are activated with fMLP in the presence of epinephrine (62). Thus, our data suggest that signaling via the a2-adrenoceptor renders neutrophils less sensitive to proinflammatory mediators.…”
Section: Discussionsupporting
confidence: 91%
“…For example, it has been recently shown that epinephrine enhances platelet-neutrophil adhesion, which is crucial for survival of critically ill patients. 26 Ortega et al 27 showed that Norepinephrine stimulated phagocytosis induced by moderate exercise. Garcia et al 28 showed in 2003 that noradrenaline modulates the phagocytic process of macrophages and maintains the phagocytic functions at physiologically optimal levels.…”
Section: Discussionmentioning
confidence: 98%
“…Sympathetic overstimulation in an LPS-induced sepsis model reportedly lead to sympathetic-vagal disequilibrium [39]. Furthermore, almost all immunocompetent cells have adrenergic receptors [40], and catecholamines exhibit substantial immunomodulatory effects [41][42][43][44]. Considering this close relationship between the autonomic nervous system and immune response, there may be two alternative explanations for the inhibitory effect of tropisetron on induction of both cytokines and catecholamines observed in the present study: 1) tropisetron modulated autonomic nervous activity to inhibit cytokine production; or 2) tropisetron inhibited cytokine production to modulate autonomic nervous activity and thereby inhibit catecholamine induction.…”
Section: Discussionmentioning
confidence: 99%